Persepsi Mahasiswa dalam Pembelajaran Online* *Pengembangan teori dari penelitian berjudul “persepsi mahasiswa terhadap materi ajar pada pembelajaran online” yang telah dipublikasi di Jurnal Eduscience Vol. 3/1 - Nuryansyah Adijaya (Wanastra: Jurnal Bahasa dan Sastra, 2018)
Internet connection has become inseparable part in modern life because it can help people do their activities easier in many areas of work, including in education. Thus, many education practitioners and institutions create online learning to support their learning-teaching process. Online learning is also considered more practical to hold learning teaching activities because it does not need a classroom to run the activities. So, lecture and students can create a class from different place. However, online learning faces some problems in its application; student’s interaction and learning environment. Therefore, this study is intended to explore those problems based on students’ perception. Survey research with Likert scale technique was used to get the data by giving 100 students questioners. But, only 54 students returned the questioners. Based on the questioners that have been analyzed, researchers found that students face some problems to interact, not only with other students but also with lecturer. It is shown by high percentage of students’ disagreement to statements that declare students’ interaction in online class already support them in learning process. Likewise learning environment, students feel that learning environment in online learning less support them in learning teaching process. Thus, to help students develop their interaction and learning environment, lecturers can facilitate them by creating a group in social media to interact and boost learning environment atmosphere among class members. Keywords: Online learning, Student’s interaction, Learning environment